Ranchers' Perspectives on Participating in Non-lethal Wolf-Livestock Coexistence Strategies - Bogezi, Carol; van Eeden, Lily M.; Wirsing, Aaron J.; Marzluff, John M. (Frontiers in Conservation Science, 2021)
Potential impacts to rural livelihoods by large carnivores, such as gray wolves (Canis lupus), increase economic liability and fear among residents, resulting in social conflicts over wildlife issues. Strategies have been developed to promote nonlethal predator management in rural communities, but there is limited understanding of why ranchers choose to participate in such programs. We conducted semi-structured interviews of ranchers in Washington state (n=45), USA, asking open-ended questions to explore their perspectives on conflict mitigation. Interviews were analyzed using Grounded Theory. Ranchers mentioned five broad types of mitigation strategies: legal measures (i.e., calling the state agency in charge of wolf management to request either compensation or lethal wolf removal), biological measures (e.g., use of guard animals), physical measures (e.g., fences), human interference (cowboys and cowgirls), and indirect measures (e.g., husbandry practices). Motivations for participating in non-lethal mitigation strategies included previous positive interactions with wildlife agency officials, an understanding of the importance of wolves to the ecosystem, and clearly outlined guidelines on how to deal with wolf interactions. Barriers that hindered rancher participation included disdain for regulation both regarding the Endangered Species Act and the state’s requirements for accessing damage compensation, which were perceived to be extensive. Negative attitudes toward wolf recovery included fear of wolves and perceived damage that wolves inflict on rural lives and livelihoods. Ranchers’ motivations and perceived barriers for participating in mitigation strategies included sociopolitical and economic factors. We suggest that in addition to mitigating economic loss, wildlife managers address the intangible social costs that deter ranchers’ participation in mitigation strategies through continued dialogue.